MODULUS ELASTISITAS BATAKO DENGAN PENAMBAHAN MATERIAL KARET DARI BAN BEKAS UNTUK DINDING BANGUNAN RAMAH GEMPA - 1998-2002 Rusnardi Rahmat Putra (CIVED, 2016)
The city of Padang has experienced with devastating earthquake events. Each of earhquake close related with building response. Since great shaking contributed nagaitve effect to construction such as severe damage and collapse. The main propose of this research is how the elasticity of batako (material for wall). We added rabber of waste tire to Batako with several percentage of weight such as 1%, 2% and 3% and its age 7, 14 and 28 days . The obtained results  is the modulus of elasticity is 1915.67 MPa in avarage, this elasticty is more convinient used to increse resistant earthquake compared with normal brick (Batako)as2237,5 MPa.